An efficient algorithm for reasoning over OWL EL ontologies with nominal schemas. (16th May 2022) - Carral, David; Zalewski, Joseph; Hitzler, Pascal
Abstract: Nominal schemas have been proposed as an extension to Description Logics (DL), the knowledge representation paradigm underlying the Web Ontology Language (OWL). They provide for a very tight integration of DL and rules. Nominal schemas can be understood as syntactic sugar on top of OWL. However, this naive perspective leads to inefficient reasoning procedures. In order to develop an efficient reasoning procedure for the language ELV^++, which results from extending the OWL profile language OWL EL with nominal schemas, we propose a transformation from ELV^++ ontologies into Datalog-like rule programs that can be used for satisfiability checking and assertion retrieval. The use of this transformation enables the use of powerful Datalog engines to solve reasoning tasks over ELV^++ ontologies. We implement and then evaluate our approach on several real-world, data-intensive ontologies, and find that it can outperform state-of-the-art reasoners such as Konclude and ELK. As a lesser side result we also provide a self-contained description of a rule-based algorithm for EL^++, which does not require a normal form transformation.